Frequency of Low Cardiac Output Syndrome Following on Pump Coronary Artery Bypass Grafting Surgery and it’s Association with Degree of Pre-operative Left Ventricular Dysfunction - Rana, KB; Ansari, A; Sharma, P; Yadav, L; Shahbaz, A (Kathmandu University Medical Journal, 2023)
Background Low cardiac output syndrome (LCOS) is a serious complication after coronary artery bypass grafting (CABG) surgery. It is associated with 10 times to 17 times increase in mortality and markedly increase morbidity.Objective To find out the frequency of Low cardiac output syndrome following on pump coronary artery bypass grafting surgery, to determine the association of Low cardiac output syndrome with degree of pre-operative left ventricular dysfunction and to compare in hospital outcomes of coronary bypass surgery with and without low cardiac output syndrome.Method This prospective, descriptive study enrolled 200 patients who underwent on pump coronary artery bypass grafting surgery using antegrade St Thomas blood cardioplegia. Pre-operatively grouped into two groups consisting Group A of 100 patients with pre-operative left ventricular ejection fraction (LVEF) ≥ 40% and group B of 100 patients with pre-operative left ventricular ejection fraction (LVEF) < 40%. Post-operatively frequency of low cardiac output syndrome was compared between the groups and in-hospital outcomes were studied.Result The mean age of the patients in the study was 53.50±7.57 years. Male to female ratio was 1.8:1. Results showed overall frequency of low cardiac output syndrome was 21.5%. The frequency of LCOS was 15 vs 28% (p - 0.038) in patients with pre-operative LV EF ≥ 40% and < 40% respectively. The outcomes of coronary artery bypass grafting surgery were stroke (3.82 vs. 30.23%, p - 0.001), acute kidney injury (5.09 vs. 23.25%, p - 0.001), respiratory failure (6.36 vs. 34.88%, p - 0.001), ICU stay days (4.75 ± 1.28 vs. 7.44 ± 4.66, p - 0.018), hospital stay days (9.56 ± 2.40 vs. 15.22 ± 3.89, p - 0.001) and mortality (4.45 vs. 32.55%, p - 0.001) in patients without and with low cardiac output syndrome respectively.Conclusion The frequency of low cardiac output syndrome following coronary artery bypass surgery is 21.5%. Left ventricular dysfunction pre-operatively is associated with high frequency of low cardiac output syndrome following surgery. There is significantly poor outcome of coronary artery bypass surgery with low cardiac output syndrome in terms of stroke, respiratory failure, acute kidney injury, mortality and significant ICU stay, hospital stay in compare to patients without low cardiac output syndrome.